The regional policy of Bulgaria and the European city - Tsvetka STOENCHEVA (Smart Cities and Regional Development Journal)
The present article aims at presenting the types of regional policy and through their comprehensive implementation to contribute to improving the living standard of the people. Regional policy in Bulgaria has its own peculiarities. They are the result of changes in the country's economic system in 1989. The institutions, economic and financial instruments for conducting an effective and efficient regional policy are indicated. The implementation of all types of regional policy are a prerequisite for the development of settlements and of cities in modern European in particular. Big cities are a driving force in the development of the European Union.